Survey mothers\' attitude and health behaviors about prevention of iron-‎deficiency in ‎‏6-24‏‎ month old children in ‎‏2005‏ - masoumeh jafari; kolsuom fadakar; mohamaali yazdani (Journal of Holistic Nursing and Midwifery)
Introduction: Iron deficiency is an important health-nutritional problem. Based of WHO ‎reports, infants and preschool children are more at risk. Children at age ‎‏6-24‏‎ months are at risk ‎of iron-deficiency.‎